Asymptotic Stability for Some Types of Nonlinear Fractional Order Differential-Algebraic Control Systems - Hasan, Sameer Qasim (Iraqi Journal of Science, 2021)
The aim of this paper is to study the asymptotically stable solution of nonlinear single and multi fractional differential-algebraic control systems, involving feedback control inputs, by an effective approach that depends on necessary and sufficient conditions.